Effect of initiating system on the structure and properties of hydrogels based on polyvinylpyrrolidone copolymers - Гриценко, Олександр Миколайович; Суберляк, Олег Володимирович; Гнатчук, Наталія Михайлівна (Eastern-European Journal of Enterprise Technologies, 2013)
The paper gives the results of studying the copolymerization of 2-hydroxyethylmethacrylate with polyvinylpyrrolidone in the presence of two-component initiating systems FeSO4 - radical initiator. Benzoyl peroxide, potassium persulfate and azo-bis-izobutyric acid dynitryl were used as radical initiators. The main purpose of the research was to investigate the effect of the nature of initiating system, namely the type of radical initiator, on forming copolymers of polyvinylpyrrolidone and to define the possibility of their use as matrices for metals recovery by chemical method. The results of research of polymerization kinetics, structural parameters of network, structure of copolymers and properties of the obtained hydrogels showed that by changing the nature of initiating system, depending on the needs, it is possible to regulate the viability of original composition, porosity, strength properties of hydrogels and swelling ability in the water. By the example of silver, new metal-filled hydrogel composites were obtained by means of modification of synthesized materials using the method of chemical recovery of metals from their salts in the hydrogel matrix. The obtained results will be used in developing the production technology of HEMA-PVP copolymers and composite metal-hydrogels based on them.